Homework Policy and Student Choice: Findings from a Montessori Charter School - Scott, Catherine M; Glaze, Nelda (Journal of Montessori Research, 2017)
The use of homework has been a controversial topic in education for many years: what types of homework to give, how much, and how often. In previous years, Ocean Montessori School (a pseudonym), the site of this study, offered homework like that of traditional public schools, such as worksheets and rote skill practice. Feeling conflicted about the misalignment between traditional homework and Montessori practices, the school administration changed the homework policy for the 2016–2017 academic year. The new policy encouraged students to choose what they wanted to do each night for homework. This study examines the views and practices of the teachers, students, and parents involved in the new homework policy. Data were collected from parent surveys, teacher focus groups, student interviews, observations, and student work samples. The findings indicate that, although students enjoyed the proposed homework change, it lacked sufficient structure for parents, and students needed support from teachers and parents to engage in meaningful homework tasks.